Traffic noise drives an immediate increase in call pitch in an urban frog. (9th January 2021) - Higham, V.; Deal, N. D. S.; Chan, Y. K.; Chanin, C.; Davine, E.; Gibbings, G.; Keating, R.; Kennedy, M.; Reilly, N.; Symons, T.; Vran, K.; Chapple, D. G.
Abstract: Noise pollution is an underappreciated component of global environmental change and can impact species that have a strong reliance on acoustic communication. In urban areas, traffic noise can interfere with the ability of animals to communicate and complete essential aspects of their daily lives. We investigated the impact of traffic noise on the calling behaviour of the brown tree frog ( Litoria ewingii ) in south‐eastern Melbourne, the fastest‐growing human population centre in Australia. We placed six acoustic recorders at increasing distances from a busy suburban road and recorded the calling behaviour (call pitch and call rate) of brown tree frogs immediately before and after loud traffic noises, and in response to different chorus sizes. Traffic noise resulted in a significant, but short‐term, increase in call pitch in the brown tree frog. Both call pitch and call rate decreased with increasing distance from the road, yet traffic noise still resulted in increased call pitch even 200–300 m from the road. Conversely, although traffic noise increased call pitch across all chorus sizes of the brown tree frog, larger chorus sizes were associated with decreased call pitch. Our study highlights the pervasive, and sustained, impact that anthropogenic noise can have on urban frog populations. Abstract : In urban areas, traffic noise can interfere with the ability of animals to communicate. We investigated the impact of traffic noise on the calling behaviour of the brown tree frog. Traffic noise resulted in a significant, but short‐term, increase in call pitch in the brown tree frog.